Innovation in small and medium-sized enterprises. (1st January 2003) - Andreassi, Tales
The purpose of this paper is to discuss and analyse some topics that characterise innovation in small enterprises, aiming to provide a theoretical landmark to be used by more empirically oriented research. The topics discussed in this paper are the innovative activities related to small businesses, the advantages and disadvantages of small businesses from the innovation perspective, the influence of venture capital, the importance of strategic alliances as a supplementary factor to the innovative effort and finally the government's role as a stimulator of innovation in small businesses.